FILOSOFI RITUAL ADUS KEMBANG PITUNG RUPA DAN NILAI KUASA PEREMPUAN PADA TRADISI LISAN DI WATUGEDE - Ardhani Endriaswari; Budi Waluyo (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2026)
The oral tradition of the Watugede Bathing Pool recounts the meeting between Ken Dedes and Ken Arok, which serves as the basis for the Adus Kembang Pitung Rupa ritual. This study aims to describe the philosophy of the ritual's stages, the meaning of the ubarampe, and the values of female power reflected in it. In addition, it aims to develop its relevance as a teaching material for Javanese language learning. This study uses a descriptive qualitative method with purposive sampling. Data were obtained through interviews, observations, and literature studies, then analysed using the interactive model of Miles and Huberman. The results show that each stage of the ritual and ubarampe embodies values of self-purification, prayers for safety and hope, as well as the meaning of women's roles in the legitimacy and sustainability of culture. These findings are implemented as a learning model in the form of descriptive text teaching materials in the learning outcomes of the Siswa Saged Nyemak Waosan Dheskriptip Ngenani Paguyuban ing Masarakat Jawa. This learning achievement opens up space for critical discussion of oral traditions that are beginning to be forgotten, while also clarifying the understanding that ritual practices are not necessarily seen as heretical but can be read as cultural heritage that carries educational values.